2019
DOI: 10.1111/trf.15159
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic properties of cold‐stored whole blood leukoreduced using a platelet‐sparing versus a non–platelet‐sparing filter

Abstract: BACKGROUND Whole blood (WB) is an appealing alternative to component‐based transfusion in patients with significant bleeding. Historically, WB was transfused less than 48 hours after collection and was not leukoreduced (LR). However, LR components are now standard in many hospitals and LR WB is desirable. We investigated the effect of the type of LR filter used, as well as storage duration, on coagulation laboratory testing of WB. STUDY DESIGN AND METHODS Ten units of LR WB—5 units manufactured with a Food and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 32 publications
9
29
0
3
Order By: Relevance
“…Indeed, while originally PLTs were stored under refrigerated conditions, in the 1970's banking practices for this component started to change, owing to the appreciation that PLTs stored at room temperature would circulate longer in the bloodstream of the recipient . Transfusion of PLTs with longer circulation times are beneficial in the prevention of bleeding and reduce the frequency of prophylactic interventions based on PLT transfusion, thus mitigating the risk of alloimmunization in patients with hypoproliferative thrombocytopenia . On the other hand, storage at 20 to 24°C under constant agitation for 5 to 7 days increases the risk of bacterial growth, resulting in 1:5000 units at risk for bacterial contamination…”
mentioning
confidence: 99%
“…Indeed, while originally PLTs were stored under refrigerated conditions, in the 1970's banking practices for this component started to change, owing to the appreciation that PLTs stored at room temperature would circulate longer in the bloodstream of the recipient . Transfusion of PLTs with longer circulation times are beneficial in the prevention of bleeding and reduce the frequency of prophylactic interventions based on PLT transfusion, thus mitigating the risk of alloimmunization in patients with hypoproliferative thrombocytopenia . On the other hand, storage at 20 to 24°C under constant agitation for 5 to 7 days increases the risk of bacterial growth, resulting in 1:5000 units at risk for bacterial contamination…”
mentioning
confidence: 99%
“…38 Although the first comparative study of WB versus standard component therapy was proposed for civilian trauma resuscitation in 2009, 1 there are only a few retrospective comparative studies of CSWB with fixed ratio or standard resuscitation for urban civilian populations and only one randomized controlled trial (RCT) (►Table 2). The other published papers concerning the civilian use of WB for 12,28,[35][36][37] trauma are either editorials or descriptive papers on the feasibility and applicability of military far-forward WB use for trauma resuscitation generally. [3][4][5][6][7][30][31][32][40][41][42][43][44] These data-from a combined total of only 586 civilian patients-form the basis of recent widespread adoption of WB use in the United States prehospital and hospital environments in urban areas, with short transport times.…”
Section: The History Mechanistic Rationale and Pathophysiology Of Tmentioning
confidence: 99%
“…These have been resolved since 2018 with the use of "low-titer" group O WB after the changes to the AABB standards in that year. 35 However, the viability of cold-stored platelets is more nuanced since studies of WB have demonstrated that platelet counts decline significantly in the first week of cold storage, even though platelet aggregation and thromboelastographic parameters remained stable. Furthermore, WB units have variability in hemostatic properties.…”
Section: Blood Banking Concerns and Costs Of Wb Transfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet aggregation in CWB evaluated by shear forces (PFA‐100) also maintained aggregation for 14 days when leucoreduced with platelet‐sparing methods but not when platelets were removed . Aggregation evaluated by agonist‐induced aggregation is reduced, but persistent, beyond day 10 .…”
Section: Functionality Of Platelets In Vitro and In Vivomentioning
confidence: 99%